12 Differences between overweight/obese patients and normal weight patients with stable heart failure. A possible link to survival benefit. (28th September 2016) - Pharithi, R; Egom, E; Maher, V; Fall, S; Fahy, S; Jago, A; Cagney, F; Murphy, C; Maher, A
Abstract : Background: Chronic heart failure (CHF) patients with increased body mass index (BMI) (overweight and obese) have better survival rates than their normal weight counterparts. There is no clear consensus about what factors-related to increased BMI underlie this benefit hence more studies are encouraged. Objective: We aimed to assess how body composition, diet, exercise levels and functional capacity differed between obese/overweight and normal weight patients. Methods: 106 patients with chronic stable heart failure were categorised according to their BMI. Anthropometric measurements, body composition (Tanita), fat mass and free Fat mass, dietary 3 day records and functional assessments including 6 minute walk test, 3 day FitBit records and NYHA class were recorded (Table 1 ). Results: There were no differences in daily energy, fat, or carbohydrate consumption or activity levels between the groups. However, overweight and obese CHF patients have significantly increased fat mass, % fat, free fat mass and consumed more protein. Mean age 66.8 ± 12.7. 72.2% (n = 78) were male and 27.8% (n = 30) were female. Conclusion: Our study highlights that energy intake and activity levels do not differ significantly between overweight/obese and normal weight patients. However, the higher fat free mass and protein intake suggests differences in protein metabolism may be relevant to the survival benefit with higher BMI.